Use of Pegylated Interferon Alpha-2a in Cutaneous T-cell Lymphoma: A Retrospective Case Collection - Janika Gosmann; Rudolf Stadler; Koen D. Quint; Ralf Gutzmer; Maarten H. Vermeer (Medical Journals Sweden, 2023)
Mycosis fungoides and Sézary syndrome are rare and largely incurable types of cutaneous T-cell lymphoma with limited therapeutic options. In 1984 Bunn et al. reported that interferon alpha is an efficient monotherapy in cutaneous T-cell lymphoma and 14 years later it was shown in a prospective, randomized trial that a combination of interferon alpha and psoralen plus ultraviolet A therapy (PUVA) is most efficient in the treatment of cutaneous T-cell lymphoma. Since then interferon alpha as single agent or, most often, in combination with phototherapy and/or retinoids has been integrated as standard of care in cutaneous T-cell lymphoma guidelines worldwide. However, production of interferon alpha was discontinued recently worldwide and pegylated interferon alpha-2a (PEG-IFNα) has been used as an alternative therapy. In contrast to numerous interferon alpha studies, only a few studies focusing on PEG-IFNα are available. Therefore, the aim of this study was to conduct a retrospective data collection to report on the efficacy, adverse events and therapy regimens of PEG-IFNα in cutaneous T-cell lymphoma. In 28 patients with cutaneous T-cell lymphoma treated in Germany and in the Netherlands, 36% of patients achieved complete remission, 36% partial remission and 29% stable disease. Eighteen percent of patients developed adverse events during therapy, which led to the discontinuation of PEG-IFNα therapy in 2 patients. The most common concomittant therapies were oral PUVA phototherapy and local radiotherapy. In conclusion, PEG-IFNα, especially in combination with skin-directed therapies, is an effective treatment option for cutaneous T-cell lymphoma in clinical practice.